UJI DAYA HAMBAT EKSTRAK CACING TANAH (Lumbricus rubellus) TERHADAP PERTUMBUHAN BAKTERI Shigella dysentriae - Devi Nurfitria; Rusmiatik Rusmiatik (Nusantara Hasana Berdikari, 2022)
Shigellosis is a food or water-borne disease that produces an inflammatory response in the colon through enterotoxins and bacterial invasion. The earthworm Lumbricus rubellus produces an anti-bacterial substance called lumbricin l. The aim of this study was to determine the inhibition of earthworm (Lumbricus rubellus) extract against the growth of Shigella dysentriae bacteria. This study is a True Experiment with Post Test Only Control Group Design, using a Completely Randomized Design consisting of 6 treatment groups, namely extract concentrations of 20%, 40%, 60%, and 80% positive control (Ciprofloxacin) and negative control (aquabides). , with 4 repetitions. The bacterial suspension was adjusted to the standard Mc Farland turbidity 0.5. The inhibition test of earthworm extract on the growth of Shigella dysentriae bacteria in vitro showed that the earthworm extract with concentrations of 20%, 40%, 60%, and 80% was not able to inhibit the growth of Shigella dysentriae bacteria.